1995
DOI: 10.1128/aac.39.8.1824
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of growth of Histoplasma capsulatum yeast cells in human macrophages by the iron chelator VUF 8514 and comparison of VUF 8514 with deferoxamine

Abstract: Histoplasma capsulatum requires intracellular iron to survive and multiply within human and murine macrophages (M). Thus, iron chelators may be useful compounds in the treatment of histoplasmosis. In the present study we compared the efficacies of five different iron chelators with deferoxamine (DEF) for their capacity to inhibit the growth of H. capsulatum yeast cells in culture medium and within human M. Of the agents tested, only one, VUF 8514, a 2,2-bipyridyl analog, was found to be effective. VUF 8514 inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…As discussed earlier, Hc yeasts must procure intracellular iron to survive in human and murine M (28,54). Indeed, part of the mechanism by which IFN-␥ activates murine M antiHistoplasma activity is via the restriction of iron (33,55).…”
Section: Discussionmentioning
confidence: 99%
“…As discussed earlier, Hc yeasts must procure intracellular iron to survive in human and murine M (28,54). Indeed, part of the mechanism by which IFN-␥ activates murine M antiHistoplasma activity is via the restriction of iron (33,55).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors demonstrated that both DEF and CHLOR suppressed the growth of Histoplasma capsulatum yeasts in human macrophages, the effect of DEF being reversed by HTF, and the effect of CHLOR reversed by FeNTA, but not by HTF (41). Several studies utilizing other drugs that interfere with iron metabolism, demonstrated the importance of iron on the multiplication and survival of Cryptococcus neoformans (34), Trypanosoma cruzi (28,36), L. pneumophila (6,8,18), H. capsulatum (29,42), Neisseria meningitidis (22), Mycobacterium tuberculosis (37), Mycobacterium avium (20), Listeria monocytogenes (1) and P. brasiliensis (14).…”
Section: Discussionmentioning
confidence: 99%
“…Most evidence that mycobacteria residing within human macrophages require a source of Fe has been indirect through studies with other intracellular pathogens in which the host cell Fe pool has been decreased or enhanced through the addition of Fe chelators or Fe supplementation of culture medium, respectively (5,37). Conclusions drawn from such approaches may be problematic since they mediate their effects through modulations of host cell physiology rather than by directly altering microbial access to Fe.…”
mentioning
confidence: 99%